Productivity for Growth of Small and Medium Enterprises: Case of Indonesian Capital Market - Ossi Ferli; Enny Hatyanti; Sara Immanuella; Dessy Ataulina; Muh. Nurdin Nur Abdi Kasman; Vasanti Etenia Kusuma (Westscience Press, 2025)
This study aims to analyze the effect of profitability, productivity, debt, age, and company size on the growth of Small and Medium Enterprises (SMEs) listed on the Indonesia Stock Exchange (IDX) on the Acceleration Board and Development Board during the period 2021–2023. Using the panel data method and the Common Effect Model (CEM) approach, this study found that only the productivity variable has a positive and significant effect on company growth, both for SMEs listed on the Acceleration and Development Boards. Meanwhile, the profitability, debt, age, and company size variables did not show a significant effect on growth. These results emphasize the importance of operational efficiency and asset optimization compared to dependence on profits or external financing in driving SME growth. These findings are expected to be strategic input for business actors, investors, and regulators in formulating policies that support strengthening the SME sector in the capital market.